Malaysia China Cultural Arts Festival showcases the cultural heritage of the two countries - Siti Nurfarmy, Ibrahim (2019)
The organizing of the Malaysia–China 2019 Cultural Arts Festival held in conjunction with the launch of the Confucius Institute (CI) UMP is not only seen to enhance Mandarin language skills and provide cultural exchange but also to strengthen good relations between the two countries and collaboration between UMP and its strategic partner, Hebei University, China.